Serum GDF15, a Promising Biomarker in Obese Patients Undergoing Heart Surgery - Sarkar, Shreya; Legere, Stephanie; Haidl, Ian; Marshall, Jean; MacLeod, Jeffrey B.; Aguiar, Christie; Lutchmedial, Sohrab; Hassan, Ansar; Brunt, Keith R.; Kienesberger, Petra; Pulinilkunnil, Thomas; Légaré, Jean-François (Frontiers in Cardiovascular Medicine, 2020)
Background: Obesity is a risk factor that negatively impacts patient outcomes undergoing heart surgery by mechanisms that are not well defined nor predicated on BMI alone. This knowledge gap has fuelled a search for biomarkers associated with cardiovascular disease that could provide clinical insight to surgeons. One such biomarker is growth differentiation factor15(GDF15), associated with inflammation, metabolism and heart failure outcomes but not yet examined in the context of obesity and cardiac surgery outcomes. Methods: Patients undergoing open-heart surgery were consented and enrolled for blood and tissue (atria) sampling at the time of surgery. Biomarkers analysis was carried out using ELISA and western blot/qPCR respectively. Biomarkers screening was classified by inflammation(NLR, GDF15, Galectin3, ST2, TNFR2), heart failure(HF) /remodeling(NT-proBNP) and metabolism(glycemia, lipid profile). Patients were categorized based on BMI: obese group (BMI ≥30.0) and non-obese group(BMI 20.0- 29.9). Subsequent stratification of GDF15 high patients was conservatively set as being in the 75th percentile. Results: A total of 80 patients undergoing any open-heart surgical interventions were included in the study. Obese (mean BMI= 35.8, n=38) and non-obese (mean BMI= 25.7, n=42) groups had no significant differences in age, sex or co-morbidities. Compared to other biomarkers, plasma GDF15 (mean 1736 vs. 1207ng/l, p< 0.001) was significantly higher in obese patients compared to non-obese. Plasma GDF15 also displayed a significant linear correlation with BMI (R2= 0.097; p= 0.0049). Atria tissue was shown to be a significant source of GDF15 protein and tissue levels significantly correlated with plasma GDF15 (R2= 0.4, p= 0.0004). Obesity was not associated with early/late mortality at median follow-up >2years. However, patients with high GDF15 (>1580ng/l) had reduced survival (65%) compared to the remaining patients with lower GDF15 levels (95%) by Kaplan Meier Analysis (median >2 years; p=0.007). Conclusions: Circulating GDF15 is a salient biomarker likely sourced from heart tissue that appears to predict higher risk obese patients for adverse outcomes. More importantly, elevated GDF15 accounted for more sensitive outcome association that BMI at 2 years post-cardiac surgery, suggesting it heralds links to pathogenicity and should be actively studied prospectively and dynamically in a post-operative follow-up.